Cellular characteristics of sputum from patients with asthma and chronic bronchitis. Issue 9 (September 1989) - Gibson, P G; Girgis-Gabardo, A; Morris, M M; Mattoli, S; Kay, J M; Dolovich, J; Denburg, J; Hargreave, F E
Abstract : The reproducibility of sputum cell counts was examined and the cell counts in patients with asthma were compared with those in patients with chronic bronchitis. Three groups of subjects were studied. Sputum from eight patients with chronic asthma and with sputum production were studied to determine the reproducibility of sputum cell counts. The findings in 10 non-smokers with asthma uncomplicated by other airway disease examined at the time of an exacerbation with sputum (group 2) were compared with those from eight smokers with chronic cough and sputum but no features of asthma (group 3). Sputum plugs were selected by microscopy to ensure their origin from the lower respiratory tract. A total cell count was performed on a trypsinised suspension, and differential and metachromatic cell counts were performed on undiluted plugs. The within specimen and test-retest reproducibility of these measurements was high (reliability coefficient, R, = 0.99 and 0.89). The sputum of the asthmatic patients was characterised by eosinophilia (69%, range 46-92%) and the presence of formaldehyde blockable metachromatic cells (1.5%, range 0.6-2.8%). In comparison, the sputum of the patients with chronic bronchitis had few eosinophils (0.5%) or metachromatic cells (0.14%); the dominant cell type was the macrophage (83%). It is concluded that sputum cell counts are reproducible in the short term, the inflammation of asthma is characterised by eosinophilia and metachromatic cells in sputum, and sputum may provide a useful source of cells for investigating the cellular characteristics of airway inflammation.